Community-Based Health Screening Initiative: Implementing Non-Invasive Diagnostic Technology for Blood Glucose, Cholesterol, and Uric Acid Detection in Rural Indonesia - Fahira Septiani; Alvania Nabila Tasyakuranti; Heni Sumarti; Affa Ardhi Saputri (Community Research and Application Journal (CRAJ), 2025)
This study presents a comprehensive community service initiative aimed at improving healthcare accessibility through free health screening services in Krandon Village, Guntur District, Demak Regency. The program implemented both conventional invasive and innovative non-invasive diagnostic technologies to measure blood glucose, cholesterol, and uric acid levels among rural community members. The initiative was conducted through a collaborative effort between the Physics Department of Universitas Islam Negeri Walisongo Semarang and the community organization Ngabdi Neliteni Ngabekti (N3). The program successfully demonstrated the practical application of university research in addressing community health needs while introducing innovative diagnostic technologies that enhance patient comfort and reduce medical waste. This community-based screening approach facilitated early detection of chronic diseases such as diabetes, cardiovascular disease, and gout, while simultaneously providing health education to promote sustainable lifestyle changes. The results highlight the potential of university-community partnerships in bridging the gap between academic research and practical healthcare solutions for underserved populations.